Pendidikan Kesehatan Perilaku Hidup Bersih dan Sehat di Sekolah Dasar: Literature Review Naratif Berbasis Bukti Ilmiah 2021-2025 - Ria Damayanti; Elvi Juliansyah; Sohibun Sohibun (Indo Publishing, 2026)
Clean and Healthy Living Behavior (PHBS) is one of the most strategic health promotion strategies to be implemented from elementary school age, between the ages of 6 and 12, during the period of habit formation that persists into adulthood. This article aims to review the latest scientific evidence regarding the effectiveness of PHBS health education in elementary schools. The method used is a narrative literature review by searching articles in Scopus, PubMed, Wiley Online Library, Web of Science, and Springer databases published between 2021 and 2025, supplemented by national literature as supporting context. The review results indicate that school-based health education interventions have consistently been shown to improve student knowledge, although changes in attitudes and practices tend to be slower and are greatly influenced by the availability of facilities, teacher and parent support, and program sustainability. Participatory methods, audiovisuals, and approaches based on behavior change theory have proven superior to conventional lecture methods. In conclusion, the success of PHBS health education in elementary schools requires a multicomponent approach involving students, teachers, parents, health workers, and ongoing support from school facilities and policies.